Advances in experimental social psychology Volume 31 - Zanna, Mark P.; ScienceDirect eBooks (San Diego : Academic Press, 1999)
Advances in Experimental Social Psychology continues to be one of the most sought after and most often cited series in this field. Containing contributions of major empirical and theoretical interest, this series represents the best and the brightest in new research, theory, and practice in social psychology.
Affect and information processing / Robert S. Wyer, Jr; Gerald L. Clore; Linda M. Isbell -- Linguistic intergroup bias: stereotype perpetuation through language / Anne Maass -- Relationships from the past in the present: significant other representations and transference in interpersonal life / Serena Chen; Susan M. Andersen -- Puzzle of continuing group inequality: piecing together psychological, social and cultural forces in social dominance theory / Felicia Pratto -- Attitude representation theory / Charles G. Lord; Mark R. Lepper -- Discontinuity theory: cognitive and social searches for rationality and normality--may lead to madness / Philip G. Zimbardo.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Social psychology; Social psychology -- Research; PSYCHOLOGY -- Social Psychology; Social psychology; Social psychology -- Research; Electronic books